1993
DOI: 10.1055/s-0038-1651617
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urokinase Type Plasminogen Activator (u-PA) in Corneal Epithelial Migration

Abstract: SummaryThe role of plasminogen activator (PA) in the migration of comeal reepithelialization was studied. Rabbit corneal blocks were cultured, and both the extent of epithelial migration over the exposed corneal stroma and the activity of PA released into the culture media were measured. A significant, direct correlation between epithelial migration and PA activity in the medium was observed, even when the migration was stimulated by fibronectin or EGF, or was inhibited by cytochalasin B or cycloheximide. Zymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 23 publications
0
31
1
4
Order By: Relevance
“…These factors are chosen in order to provide a measure of how responsive endothelial cells are to protease and to fibronectin. It is known that proteases promote the movement of endothelial cells, (Schleef and Birdwell, 1982;Roberts and Forrester, 1990;Morimoto et al, 1993;Gordon and DeMoss, 1999).…”
Section: The Principles Of Reinforced Random Walk Applied To Cell Movmentioning
confidence: 99%
“…These factors are chosen in order to provide a measure of how responsive endothelial cells are to protease and to fibronectin. It is known that proteases promote the movement of endothelial cells, (Schleef and Birdwell, 1982;Roberts and Forrester, 1990;Morimoto et al, 1993;Gordon and DeMoss, 1999).…”
Section: The Principles Of Reinforced Random Walk Applied To Cell Movmentioning
confidence: 99%
“…Plasmin activity was measured using the plasmin substrate S-2251 as follows (Friberger et al, 1978 ;Morimoto et al, 1993) : 100-µl aliquots of conditioned culture media were mixed in each well of a 96-well plate with 20 µl plasminogen solution [10 µg ml −" in Tris-buffer (50 m Tris, pH 7n4, with 0n01 % Triton X-100)], and incubated at 37mC with 100 µl of 0n06 m S-2251 solution. The release of p-nitroanilide was measured by reading optical density at 405 nm with a microplate reader.…”
Section: Measurement Of Plasmin Activitymentioning
confidence: 99%
“…ProuPA can be converted to active enzyme by traces of plasmin initiating the plasminogen activation cascade. We have recently demonstrated that uPA staining in cultured human RPE cells was localized to focal contact sites at the leading edges of cultured subconfluent RPE cells [12], a distribution typical of migrating cells [18]. TGF-ß is produced by most cultured cells in a latent form which can be converted to the biologically active molecule by plasmin [19].…”
Section: Resultsmentioning
confidence: 99%